2016
DOI: 10.1007/978-3-319-38810-6_21
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Cerebral Oxyhaemoglobin Signal and Physiological Signals During Cycling Exercise: A Near-Infrared Spectroscopy Study

Abstract: Near-infrared spectroscopy (NIRS) is a widely used noninvasive method for measuring human brain activation based on the cerebral haemodynamic response. However, systemic changes can influence the signal's parameters. Our study aimed to investigate the relationships between NIRS signals and skin blood flow (SBF) or blood pressure during dynamic movement. Nine healthy volunteers (mean age, 21.3 ± 0.7 years; 6 women) participated in this study. The oxyhaemoglobin (O2Hb) signal, SBF, and mean arterial pressure (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…A correlation between MAP and [O 2 Hb] (or StO 2 ) has been reported in various functional studies [ 89 , 98 , 99 ]. Tsubaki et al investigated the relationships between NIRS signals and MAP during exercises on a bicycle ergometer [ 100 ]. They found highly significant correlations between MAP and [O 2 Hb] during warm-up and at workloads corresponding to 30 and 50% of peak oxygen consumption [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation between MAP and [O 2 Hb] (or StO 2 ) has been reported in various functional studies [ 89 , 98 , 99 ]. Tsubaki et al investigated the relationships between NIRS signals and MAP during exercises on a bicycle ergometer [ 100 ]. They found highly significant correlations between MAP and [O 2 Hb] during warm-up and at workloads corresponding to 30 and 50% of peak oxygen consumption [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tsubaki et al investigated the relationships between NIRS signals and MAP during exercises on a bicycle ergometer [ 100 ]. They found highly significant correlations between MAP and [O 2 Hb] during warm-up and at workloads corresponding to 30 and 50% of peak oxygen consumption [ 100 ]. In another recent study, in contrast, a non-significant association between StO 2 and MAP was observed in critically ill adults [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies revealed exercise-induced activations in prefrontal cortex (PFC) showing that Hb and HHb levels respond as a function of both exercise load and duration in both experts (Rupp et al 2008) and non-experts (Auger et al 2016; Giles et al 2014; Jung et al 2015). However, previous studies focusing on neurovascular coupling at several intensity levels show that there is no consensus concerning the type of exercise (incremental tests with short stages vs. constant-load exercises), duration of exercise (Giles et al 2014; Tsubaki et al 2016) and intensity (Auger et al 2016; Byun et al 2014; Giles et al 2014; Takehara et al 2017; Tsubaki et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The timepoint of significant increase in the O 2 Hb and THb were 50-60% during incremental exercise, while the SBF was 70% during incremental exercise (Figure 3). Moreover, previous studies reported none or negative correlation between the SBF and O 2 Hb at high intensity exercise and cool-down (Tsubaki et al, 2016;Kojima et al, 2021). Although SBF and O 2 Hb appear to increase simultaneously, we considered that changes in cerebral oxygenation were related to increased cerebral blood flow or cortical activation.…”
Section: Cerebral Oxygenation During Incremental Exercisementioning
confidence: 97%